Gender Differences and their Impacts on Students’ Performance in Speaking Ability - Erviona, Lussy; Arsyad, Safnil (Journal of English for Specific Purposes in Indonesia, 2022)
This study aims to see the differences of the ability in speaking English between male and female students at the senior high school level. This study employed descriptive quantitative research. The study was conducted at SMAN 1 Bengkulu Selatan. There were ten male students and ten female students of senior high school Bengkulu Selatan, Bengkulu, Indonesia, as the samples of this study, therefore the researcher focused on using 20 students as the data source. The activities carried out by researcher in data collection were by giving and recording 3 (three) minutes session of speaking activities about student personal experience. Then the data were rechecked, evaluated, and corrected. The researcher used assessment indicators, namely: pronunciation, vocabulary, grammar, fluency, and understanding. The results were described in the form of numbers, properties, and characteristics. The result of this study showed that between male and female students, female students were  better that male students in the speaking as seen from the results of comprehension, vocabulary, and pronunciation. On the other hand, male students had better scores in grammar and fluency. From the result, it can be concluded that both male and female students at SMAN 1 Bengkulu Selatan were fluent to speak English based on different indicators.